Automated and quantitative data extraction of walls and slabs from before-and after-remodeling floor plans - Kim, Seong Ah; Seo, Wonseok; Kim, Jinyoung (Journal of the Architectural Institute of Korea, 2021)
It is estimated in 2020 that over 2.4 million houses in Korea are aged more than 30 years. This means that over 40% of the entire houses in Korea are considerably aged. Two options could be taken to improve the poor residential environment: either reconstruction or remodeling. Compared to reconstruction, remodeling has advantages on the construction period and cost. In addition, remodeling is environmentally friendly; and therefore, current regulation is favorable to remodeling over reconstruction. During the early stages of the apartment remodeling project, many candidate floor plans are presented. In order for the evaluation of those multiple candidate plans, extracting information regarding bearing walls and other structural elements from the plans is critical. Accordingly, an automated and quantitative data extraction system for walls and slabs from before-and after-remodeling floor plans is developed. With the developed program, it is possible to analyze and visualize bearing walls, non-bearing walls, slabs, and weight alterations after remodeling in a rapid and automated manner.
Keywords: Automated floor plan evaluation; CAD; Remodeling; Apartment house; Revit add-on